ARKEOPRENEURSHIP SEBAGAI ALTERNATIF PEMANFAATAN HASIL PENELITIAN ARKEOLOGI MEMBANGUN PARIWISATA CAGAR BUDAYA NASIONAL - Asyhadi Mufsi Sadzali (SANGIA: Jurnal Penelitian Arkeologi, 2023)
The results of archaeological research in Indonesia have been published in the form of research reports, scientific articles, seminar proceedings, and reference books, as well as in the form of audiovisuals. However, there is minimal absorption in the public sphere, and is considered difficult to accept, understand, and enjoy the general public. Research results should be used in various forms, and dimensions at all levels of society in line with the theory of the "Holtorf Model" by Cornelius Holtorf (2007), which views that the results of archaeological research must be communicated, and utilized in various ways through networking support to provide benefits. This issue is the background of the research, namely how to use the results of archaeological research case studies of the Muarajambi National Cultural Heritage Area which has a direct impact on the general public, especially in tourism activities. This research is a literature study with qualitative reasoning, with stages of collecting supporting literature data, data analysis, and data interpretation to answer research questions. The results of the study found that the concept of entrepreneurship can be adopted for downstream or utilization of archaeological research results, especially entrepreneurship in the field of cultural tourism, most of which are mainly in the form of cultural materials. Expanding the use of archaeological research results is important to continue to be pursued in concrete forms that have a direct impact on the welfare of the general public both in terms of socio-cultural and economic.